2009
DOI: 10.1111/j.1365-2400.2008.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation genetics and management implications for European grayling, Thymallus thymallus: synthesis of phylogeography and population genetics

Abstract: European grayling, Thymallus thymallus (L.), populations have steadily declined since the mid-1980s, mostly because of habitat degradation and increased predation pressure. To provide guidelines for conservation strategies and future management programmes, delineation of conservation and management units is warranted. Over the last decade, several studies have investigated the phylogeography and population genetic structure of T. thymallus using mitochondrial and nuclear microsatellite DNA markers. However, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 92 publications
(270 reference statements)
1
51
0
Order By: Relevance
“…This pattern is also reflected in the probability of common ancestors (2MOD), which was much contact zone where distinct evolutionary lineages have met in diverse taxonomic groups, resulting in an overall increased genetic diversity (Taberlet et al 1998;Hewitt 2000). These patterns have also been observed in aquatic species such as grayling (Thymallus thymallus; Gum et al 2009), a fish which frequently co-occurs with freshwater pearl mussels (Geist et al 2006). The validity of the contact zone in pearl mussel could explain the high genetic diversity found in this area.…”
Section: Genetic Diversitymentioning
confidence: 86%
See 1 more Smart Citation
“…This pattern is also reflected in the probability of common ancestors (2MOD), which was much contact zone where distinct evolutionary lineages have met in diverse taxonomic groups, resulting in an overall increased genetic diversity (Taberlet et al 1998;Hewitt 2000). These patterns have also been observed in aquatic species such as grayling (Thymallus thymallus; Gum et al 2009), a fish which frequently co-occurs with freshwater pearl mussels (Geist et al 2006). The validity of the contact zone in pearl mussel could explain the high genetic diversity found in this area.…”
Section: Genetic Diversitymentioning
confidence: 86%
“…A geographical zone in central Sweden has been described as a major European contact zone for genetically divergent evolutionary lineages in many species (reviewed in Taberlet et al 1998;Hewitt 2000), including aquatic taxa and fish species (e.g. Gum et al 2009). This region was thus selected as a candidate area for studying the genetic structuring of pearl mussels and for comparing it with results on the genetic variation within and between populations from central, southern and northeastern Europe.…”
Section: Introductionmentioning
confidence: 99%
“…This divergence clearly predates the late Pleistocene period (130,000-10,000 years) implying that European grayling survived dramatic temperature oscillations in distinct refugia (see review in Gum et al 2009). Our study included 34 populations originating from the three lineages and the coalescent analyses using an hierarchical Bayesian model suggested that all grayling populations have experienced dramatic size reductions that date back 1,000-10,000 or 32,000-100,000 years, depending whether an exponential or linear population growth/decline model was used.…”
Section: Discussionmentioning
confidence: 97%
“…European grayling (Thymallus thymallus) are widely distributed over Northern Europe and Russia, extending from Wales in the West to the Ural mountains in the East and have undergone significant declines in numbers in many populations due to environmental degradation and overexploitation (Gum et al 2009). Conservation assessments made during the 1980s concluded that the species was endangered in the UK and threatened within Europe (Lelek 1984) and in an effort to conserve the species, stocking has been implemented in a number of European countries (Ibbotson et al 2001;Sušnik et al 2004;Gum et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, continuing habitat degradation and over-fishing at the local scale mean that the active conservation of grayling remains of pressing importance in Europe (e.g. Meldgaard et al 2003;Bergerot et al 2008;Gum et al 2009). …”
Section: Introductionmentioning
confidence: 99%